Basics and Applications of the Fusuma Sliding Flap: A Versatile Method for Reconstruction of Full-thickness Defects of the Lower Lip - Shogo Kasai; Toshiharu Minabe; Wataru Tsugu; Satoshi Fukuzumi; Kazuo Kishi (Journal of Plastic and Reconstructive Surgery, 2025)
Objectives: Many reconstruction techniques exist for full-thickness defects of the lower lip, which all have advantages and disadvantages. We performed lower-lip reconstruction using the Japanese Fusuma sliding flap method and obtained good results. Here, we introduce this method and report on its results, including long-term follow-up, and its details. Methods: A lateral advancement flap from the cheek, pedicled on the facial artery, reconstructs the lower lip. If needed, a subcutaneous flap from the cranial nasolabial fold reconstructs the donor site of the first flap. We retrospectively examined nine patients with full-thickness, full-width lower-lip defects who underwent reconstructive surgery using the Fusuma sliding flap method between 2006 and 2021. The postoperative evaluation items were as follows: (1) survival of skin flaps, (2) appearance, (3) eating function, (4) perception, and (5) presence or absence of revision surgery. Results: Regardless of the form or extent of defects, the flaps survived successfully in all cases, and their appearance, feeding function, and sensation were good. However, revision surgery was required for cases where defects exceeded the commissure. Conclusions: Although the number of cases was small, and issues that the need to be addressed remain, this procedure is simple, highly versatile, and provides stable results.